The Impact of Social Media Addiction on Teenage Depression: A Correlational Study - Ali, Muhammad; Ullah, Rizwan; Khan, Uzair; Rafique, Kiran; Obaidullah; Murad, Safia (Indus Journal of Bioscience Research, 2025)
Introduction: Teenagers’ lives revolve around social media, with platforms like Instagram, Snapchat, and TikTok shaping how they express and understand themselves. While offering connectivity, social media can negatively affect mental health, particularly causing depression. Motivation: This study explores the link between excessive social media use and depressive symptoms in teenagers, focusing on how engagement patterns contribute to emotional distress. Purpose: The study assessed social media use and depressive symptoms using surveys and the Beck Depression Inventory (BDI) to analyze the correlation between depression and social media addiction. Results: This study demonstrates concerning relationship between high social media engagement and negative emotional outcomes. Many participants also struggled to control their use of social media and were anxious, restless and experienced emotional distress when they couldn’t access it. For example, compulsive behaviors such as frequent social media checking, disrupted daily routines including sleep, academics, and interpersonal relationships. On the contrary, many participants showed depressive symptoms such as sadness, guilt, hopelessness, and lack of enthusiasm for activities. Discussion: The findings of this study underscore the impact of excessive social media use on mental health, suggesting that social media addiction may contribute to or exacerbate depressive symptoms. The results emphasize the need for promoting healthier digital habits and encouraging individuals to seek professional support when experiencing severe emotional distress related to social media use. Developing strategies to mitigate the adverse effects of excessive social media engagement and raise awareness of its mental health risks is essential for protecting teenagers’ well-being in the digital age.